Adhesion of ligand-conjugated biosynthesized magnetite nanoparticles to triple negative breast cancer cells. (April 2017) - Obayemi, John D.; Hu, Jingjie; Uzonwanne, Vanessa O.; Odusanya, Olushola S.; Malatesta, Karen; Anuku, Nicolas; Soboyejo, Winston O.
Abstract: This paper presents the results of an experimental study of the adhesion forces between components of model conjugated magnetite nanoparticle systems for improved selectivity in the specific targeting of triple negative breast cancer. Adhesion forces between chemically synthesized magnetite nanoparticles (CMNPs), biosynthesized magnetite nanoparticles (BMNPs), as well as their conjugated systems and triple negative breast cancer cells (MDA-MB-231) or normal breast cells (MCF 10A) are elucidated at a nanoscale. In all cases, the BMNPs had higher adhesion forces (to breast cancer cells and normal breast cells) than CMNPs. The adhesion of LHRH-conjugated BMNPs or BSA-conjugated BMNPs to cancer cells is shown to be about 6 times to that of normal breast cells. The increase in adhesion forces between luteinizing hormone-releasing hormone, LHRH- or EphA2, a breast specific antibody(BSA)-conjugated BMNPs to breast cancer cells is attributed to van der Waals interactions between the peptides/antibodies from the conjugated nanoparticles and the over-expressed receptors (revealed using immunofluorescence staining) on the surfaces of the breast cancer. The implications of the results are discussed for the selectivity and specificity of breast cancer targeting by ligand-conjugated BMNPs. Graphical abstract: Highlights: Ligand-conjugation of biosynthesized magnetite nanoparticles (BMNPs). Overexpression of LHRH and EPhA2 receptors on the surfaces of breast cancer. Adhesion forces of Ligand-conjugated BMNPs and CMNPs nanoparticles to breast cancer. Insights for potential screening of breast cancer ligands for specific targeting.